Capital cultural e consumo de status na classe média brasileira - Costa Filho, Custódio Genésio da (2016)
The growth of developing countries and the social ascension of a portion of its population have placed the middle class in worldwide evidence. The social consequences of status consumption of the middle class results in a rich theoretical debate. In this context, this study had the objecti ve of identifying the influence of cultural capital over status consumption standards of Brazilian middle class. The research presents qualitative and descriptive character, and was conducted with three focus groups and 18 individual semi-structured interviews with members of social classes B and C. For the data analysis, categorical thematic content analysis was used. Among the main conclusions, we highlight that class C (the so called “new middle class) seems to present no conditions to be considered middle class under the perspective of consumption. These are people who suffer with debts and with limitations, even at the level of functional consumption, and dreams of truly becoming middle class. The acquisition of an eventual item of conspicuous consumption does not confer status, given that its consumption is incomplete, it clashes and, sometimes, causes more embarrassment than status. Thus, we identified that the turning point of Brazilian consumption status seems to occur at class B (or traditional middle class). When specifically comparing groups from distinct levels of cultural capital of class B, the research concludes that there are countless status consumption differences between people from high and low cultural capital; the distinction is clearly processed in some social consumption areas, while in others the distinction is very subtle. In summary, people from low cultural capital seek status by availing themselves of material resources, while people from high cultural capital differentiate themselves using intellectual resources. Regarding the influence of global culture, we verified that it is wide-ranged and indistinct for both high and low cultural capital people. However, the differences are perceptive in international travels, in the interest and planning of the travel, in the choice of destination, in programing the travels and in the interaction with the foreigners. In simple terms, the distinction occurs by the domain of another language and the adhesion to tour packages. This work also sought to propose an evaluation criterion for the cultural capital of Brazilian society, which, combined with an economic classification, would lead to a more adequate social classification. The results show that many items must not be included, and present the useful items and the evaluation criterion.